USABILITY EVALUATION OF THE WEBSITE SERVICES USING THE WEBUSE METHOD (A CASE STUDY: PUSTAKAARSIP.KAMPARKAB.GO.ID) - Riyo Saputra; Muhammad Jazman; Syaifullah Syaifullah; Muhammad Luthfi Hamzah (Jurnal Teknik Informatika (Jutif), 2022)
This researcher aims to find the DISPERSIP website in terms of usability using Website Usability Evaluation (WEBUSE) to determine which parts need to be improved. The Kampar Regency Library and Archives Service have implemented one of the online-based library services with the implementation of a website in the library and archives section of Kampar Regency. The aim is that governance relationships involving the Government, the private sector and the community can be created to be more effective, efficient, productive and responsive. In its application, problems arise, such as incompatibility of menu names, no back button, colour differences, and inactive links and errors—an unprecedented evaluation of the website's usability. The WEBUSE method determines the usability level of a website based on the user's perspective. Data collection was carried out using a questionnaire distributed to all active members of the library with a definite website with a total of 100 respondents based on the slovin formula. Based on the results of the usability evaluation, the DISPERSIP website got a good usability level for the four categories of usability in the WEBUSE method, namely Content, Organization and Readability with a value of 0.70, Navigation and Links with a value of 0.69, User Interface Design with a value of 0.70 and Performance and Effectiveness got a score of 0.60. Overall the DISPERSIP website has good usability with a value of 0.67, and there are eight recommendations for usability improvements based on the problem.